Evaluasi Manajemen Pajak pada Perusahaan Perdagangan Besar Barang Logam untuk Bahan Konstruksi (Studi Kasus di Perusahaan PMA PT. ABC) - Yang Guoquan; Siti Nuryanah (Jurnal Impresi Indonesia, 2025)
Foreign Investment Companies (PMA) in Indonesia face significant challenges arising from the complexity and dynamics of tax regulations. This situation requires a tax management system that is not only compliant but also efficient in order to maintain the financial health of the company. This study aims to evaluate the implementation of best practice tax management at PT ABC, a PMA company operating in the wholesale trade of metal goods for construction materials. Using a qualitative approach through case study methodology, this research examines in depth the aspects of tax planning, implementation, and control within the company. Data collection was conducted through semi-structured interviews with financial managers and analysis of internal company documents. The results of the study indicate that PT ABC has a solid tax management foundation, including the use of the SAP system, documented Standard Operating Procedures (SOPs), and the implementation of routine audits. However, further identification revealed operational challenges, such as cash flow pressure due to tax refund mechanisms, high compliance costs, and a technology system that is not yet fully integrated with the tax authority's digital platform. This study recommends five strategic steps for optimization: enhancing technology integration, exploring fiscal incentives, formalizing collaboration with external consultants, developing internal tax policies, and implementing a more advanced cash flow monitoring system.